An Analysis of the Requirements for Efficient Protocols in WBAN - Shibghatullah, Abdul Samad; Al Barazanchi, Israa (2014)
Wireless Body Area Networks (WBAN) plays a major role in the advancement of technology, particularly for diagnosising the many life threatening diseases as well as providing real-time health monitoring. The objective of this paper is to study and analyze the problems of protocols in WBAN to provide the requirements related to health care in a medical environment. The protocols need to be energy efficient and reliable as well. To date, several metrics, such as channel utilization and energy efficiencies are defined. This research provides a clear outlook on the types of routing protocols and the problems related to the losses and distribution of data in a medical environment, thus meeting energy efficiency, low delay and reliability.